2003
DOI: 10.1046/j.1365-2567.2003.01560.x
|View full text |Cite
|
Sign up to set email alerts
|

CD1d‐restricted natural killer T cells are potent targets for human immunodeficiency virus infection

Abstract: Summary Invariant human natural killer T cells (NKT) express a restricted T‐cell receptor (TCR) Vα24Vβ11 repertoire. These cells share both phenotypic and functional similarities between NK and T cells. Given the emerging role of NKT cells as critical cells in bridging the gap between innate and adaptive immunity, we examined their susceptibility to productive human immunodeficiency virus (HIV) infection by T‐tropic, M‐tropic, and primary isolates of HIV. We generated three human NKT cell clones (CA5, CA29, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
2
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 42 publications
0
39
2
2
Order By: Relevance
“…39,51 Additionally, the accumulation of CD4 Ϫ iNKT cells with age could be explained by the loss of CD4 expression as a result of linear differentiation of less mature CD4 ϩ cells, as it was suggested in a recent report. 27 However, the latter possibility is not supported by the existence of stable clones of human CD4 ϩ iNKT cells 41,52,53 that maintain CD4 expression even after 8 months of continuous culture (Dr Brian Wilson, Massachusetts General Hospital, Cambridge, MA, personal communication via e-mail on June 11, 2004). Although the extent of iNKT cell peripheral expansion in mice has not been directly analyzed, small sizes of individual iNKT cell clones in periphery 54 and high frequency of V␣14i cells in thymus 25 suggest that both CD4 ϩ and CD4 Ϫ mouse iNKT cells are more dependent upon thymic output as opposed to peripheral expansion.…”
Section: Discussionmentioning
confidence: 99%
“…39,51 Additionally, the accumulation of CD4 Ϫ iNKT cells with age could be explained by the loss of CD4 expression as a result of linear differentiation of less mature CD4 ϩ cells, as it was suggested in a recent report. 27 However, the latter possibility is not supported by the existence of stable clones of human CD4 ϩ iNKT cells 41,52,53 that maintain CD4 expression even after 8 months of continuous culture (Dr Brian Wilson, Massachusetts General Hospital, Cambridge, MA, personal communication via e-mail on June 11, 2004). Although the extent of iNKT cell peripheral expansion in mice has not been directly analyzed, small sizes of individual iNKT cell clones in periphery 54 and high frequency of V␣14i cells in thymus 25 suggest that both CD4 ϩ and CD4 Ϫ mouse iNKT cells are more dependent upon thymic output as opposed to peripheral expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also reported that hepatic NK and NKT cell took part in the antimetastasis of tumor [23][24][25] . NK1.1 + cells were reported to involve in the pathogenesis of many diseases, like human immunodeficiency virus (HIV) infection and liver disease [26,27] . The demonstration that NK cell or NKT cell could give rise to liver injury had been confirmed by different groups, including our laboratory [28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…The major receptor for HIV-1 is the surface expressed CD4 and the virus mainly infects CD4-expressing T lymphocytes, monocytes/macrophages and dendritic cells (DC) that also express at least one of the co-receptors CCR5 or CXCR4 [21,22]. The CD4+ subset of NKT cells are found to express high levels of CCR5 and low levels of CXCR4, which makes them susceptible to infection by viruses preferentially using CCR5 as the co-receptor, or so-called R5-tropic strains [18,23]. Motsinger et al proved that NKT cells are much more predisposed to R5-tropic infection than other cell types by showing that GFP-tagged virus could infect up to 50% of aGalCer-activated CD4+ NKT cells in contrast to 5% of conventional CD4+ T cells, which conversely are twice as susceptible as CD4+ NKT cells to infection with an X4-tropic virus [18].…”
Section: Nkt Depletion During Hiv-1 Infectionmentioning
confidence: 99%